2016
DOI: 10.1007/s00296-016-3436-0
|View full text |Cite
|
Sign up to set email alerts
|

Tailored treatment options for patients with psoriatic arthritis and psoriasis: review of established and new biologic and small molecule therapies

Abstract: The diverse clinical picture of PsA suggests the need to identify suitable therapies to address the different combinations of clinical manifestations. This review aimed to classify the available biologic agents and new small molecule inhibitors (licensed and nonlicensed) based on their proven efficacy in treating different clinical manifestations associated with psoriasis and PsA. This review presents the level of evidence of efficacy of different biologic treatments and small molecule inhibitors for certain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 89 publications
(88 reference statements)
1
22
0
3
Order By: Relevance
“…In the same study,patients treated with cyclosporine showed a 37% mean improvement in the NAPSI score (21 (25). The efficacy of etanercept in nail psoriasis has also been supported by other studies (7,26,27). In our case, there was a rapid response to etanercept with a significant reduction in the NAPSI score.…”
Section: Case Reportsupporting
confidence: 71%
“…In the same study,patients treated with cyclosporine showed a 37% mean improvement in the NAPSI score (21 (25). The efficacy of etanercept in nail psoriasis has also been supported by other studies (7,26,27). In our case, there was a rapid response to etanercept with a significant reduction in the NAPSI score.…”
Section: Case Reportsupporting
confidence: 71%
“…TRAF3 and TRAF4 negatively regulate IL-17 signaling by competing for Act1 binding with TRAF6 and IL17RA, respectively (Wu et al, 2015, Zepp et al, 2012, Zhu et al, 2010). Although IL-17 alone regulates the expression of a relatively small subset of approximately 40 genes in cultured keratinocytes (Chiricozzi et al, 2011, Nograles et al, 2008), biologics targeting IL-17 and its receptors are very effective treatments for psoriasis (Elyoussfi et al, 2016, Lowes et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Fortunately for PsA patients, TNF inhibitors (TNFi) became available at the beginning of the millennium and have demonstrated excellent efficacy in patients with PsA 53 . Five TNFi agents are now available, including etanercept, adalimumab, infliximab, golimumab, and certolizumab 54 . Certolizumab is the most recent addition to the list and has proven to be efficacious in TNFi failures 55 .…”
Section: What Are the Advances In Therapies For Psoriatic Arthritis?mentioning
confidence: 99%
“…All have been proven to be effective for signs and symptoms as well as for preventing radiographic progression of PsA. Infliximab, golimumab, and certolizumab have been proven to be effective for enthesitis and dactylitis in pivotal randomized controlled trials (RCT), while etanercept and adalimumab have been shown to control enthesitis and dactylitis in subsequent studies 54 .…”
Section: What Are the Advances In Therapies For Psoriatic Arthritis?mentioning
confidence: 99%
See 1 more Smart Citation